2008
DOI: 10.1115/1.2950068
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Investigations of Tip Leakage Flow in Axial Flow Turbines—Part I: Effect of Tip Geometry and Tip Clearance Gap

Abstract: A numerical study has been performed to investigate the effect of tip geometry on the tip leakage flow and heat transfer characteristics in unshrouded axial flow turbines. Base line flat tip geometry and squealer type geometries, namely, double squealer or cavity and suction-side squealer, were considered. The performances of the squealer geometries, in terms of the leakage mass flow and heat transfer to the tip, were compared with the flat tip at two different tip clearance gaps. The computations were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…The inclusion of a casing recess showed positive signs of reduced tip heat transfer, however, a small effect on the aerodynamic efficiency. Additional validated numerical studies by Krishnababu et al [12] and Yang et al [13,14] showed noticeable reductions of the tip leakage vortex and tip heat transfer with the squealer tip.…”
mentioning
confidence: 99%
“…The inclusion of a casing recess showed positive signs of reduced tip heat transfer, however, a small effect on the aerodynamic efficiency. Additional validated numerical studies by Krishnababu et al [12] and Yang et al [13,14] showed noticeable reductions of the tip leakage vortex and tip heat transfer with the squealer tip.…”
mentioning
confidence: 99%
“…T i is calculated from mass-averaged total temperature at the inlet as suggested by Ameri and Bunker [25] and Krishnababu et al [10]. Average heat transfer coefficient, h, is defined as…”
Section: Thermal Investigationmentioning
confidence: 99%
“…Camci et al [9] experimentally studied the aerodynamic characteristics of partial squealer rims in the single-stage, low-speed, rotating Axial Flow Turbine Research Facility (AFTRF) of the Pennsylvania State University and found that the suction side squealer had a better aerodynamic performance with respect to cavity squealer. Krishnababu et al [10] performed a numerical investigation on the effects of blade tip geometry and found that cavity tip improved the aerodynamic performance and decreased the heat transfer rates to the blade tip. Kavurmacioglu et al [11] and Kavurmacioglu et al [12] carried out a numerical study in a rotational test rig (AFTRF) for aerodynamic performance of full-and partial-length squealer rims.…”
Section: Introductionmentioning
confidence: 99%
“…The instantaneous heat flux in the rotor crown was twice the time-averaged values due to the strong shock interactions between blade rows. Krishnababu et al (2009aKrishnababu et al ( , 2009b investigated the effect of tip geometry in part 1 and effect of relative casing motion on the tip leakage flow and heat transfer characteristics in a single blade axial flow turbine. They performed numerical study using CFX 5.6 computational software.…”
Section: Umentioning
confidence: 99%